Digital Transformation for a Sustainable Society in the 21st Century : I3E 2019 IFIP WG 6.11 International Workshops, Trondheim, Norway, September 18–20, 2019, Revised Selected Papers /: I3E 2019 IFIP WG 6.11 International Workshops, Trondheim, Norway, September 18–20, 2019, Revised Selected Papers. (2020) - Unknown
No abstract available